Evaluating health service coverage in Ghana's Volta Region using a modified Tanahashi model - Mallory C. Sheff; Ayaga A. Bawah; Patrick O. Asuming; Pearl Kyei; Mawuli Kushitor; James F. Phillips; S. Patrick Kachur (Taylor & Francis Group, 2020)
Background: The United Nations 2030 Sustainable Development Goals have reaffirmed the international community's commitment to maternal, newborn, and child health, with further investments in achieving quality essential service coverage and financial protection for all. Objective: Using a modified version of the 1978 Tanahashi model as an analytical framework for measuring and assessing health service coverage, this paper aims to examine the system of care at the community level in Ghana's Volta Region to highlight the continued reforms needed to achieve Universal Health Coverage. Methods: The Tanahashi model evaluates health system coverage through five key measures that reflect different stages along the service provision continuum: availability of services; accessibility; initial contact with the health system; continued utilization; and quality coverage. Data from cross-sectional household and health facility surveys were used in this study. Immunization and antenatal care services were selected as tracer interventions to serve as proxies to assess systems bottlenecks. Results: Financial access and quality coverage were identified as the biggest bottlenecks for both tracer indicators. Financial accessibility, measured by enrollment in Ghana's National Health Insurance Scheme was poor with 16.94% presenting valid membership cards. Childhood immunization was high but dropped modestly from 93.8% at initial contact to 76.7% quality coverage. For antenatal care, estimates ranged from 65.9% at initial visit to 25.1% quality coverage. Conclusion: Results highlight the difficulty in achieving high levels of quality service coverage and the large variations that exist within services provided at the primary care level. While vertical investments have been prioritized to benefit specific health services, a comprehensive systems approach to primary health care needs to be further strengthened to reach Ghana's Universal Health Coverage objectives.